PERILAKU HIPERAKTIF PESERTA DIDIK DAN PENANGANANNYA (STUDI KASUS DI SDN INPRES BUMI BAHARI) - Nurheda Nurheda; Rusdin Rusdin; Titin Titin (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
The aims to research on students' hyperactive behavior and its handling (case study in SDN Inpres Bumi Bahari) which is discussed into sub-problems, namely how is the behavior of hyperactive learners at SDN Inpres Bumi Bahari? What efforts have been made in handling the hyperactive behavior of students at SDN Inpres Bumi Bahari ?. This study uses a qualitative approach, data collection techniques through observation, interviews, and documentation. The results of this study indicate that the behavior of students who are hyperactive they are always difficult when invited to concentrate when the learning process, attention is easily distracted especially when he feels bored. At the time in the class, he often ran to and fro and often in and out of class for no apparent reason. They most like to disturb their friends in class. My students' various behaviors of students really train the patience of the teacher during the learning process. Efforts made in handling the behavior of hyperactive learners of a teacher are applying the rules slowly to students, helping students in learning, using positive reinforcement. Give the same treatment as other friends, warn classmates not to be antipathy towards him, put a hyperactive position in the front seat of students, do not give penalties that are too heavy, given the hyperactive punishment of students will feel more responsible for what he did. Motivating to be more enthusiastic in the learning process. The results of the study are expected that teachers must be more creative in managing the learning process so that students in SDN Inpres Bumi Bahari can concentrate well during the learning process.